Prospective audit of drug prescribing errors in a tertiary nephrology centre. (24th May 2012) - Tanwar, M; Sheikh, H; Patey, S; Matthews, S; Hothi, D
Abstract : Aims: To identify the nature of prescribing errors on the renal unit, determining type of error, timing, medication involved, prescriber and repeat offenders and risks for prescribing errors. Methods: Prospective audit of drug errors made on our electronic prescribing system (EPR) reported by pharmacists and nurses. Data collected on a data record sheet over a 2 week period on 4 occasions between August 2011 and February 2011. This period encompassed 1 time point for previous trainees (end of post) and 3 time points for subsequent trainees (start, mid-point and end of post). Results: 102 errors were identified over the 4 audit blocks (21 in August 2010, 13 in September 2011, 48 in November 2011 and 20 in February 2011).The overall approximate calculated error rate was 3.0%. 44% of errors were made during the weekday daytime shifts, 31% at night time, 11% over the weekend and 14% at evening shifts. 58% of errors were made by the SpR, 47% of which were made at night. 19% of SpR errors were related to paracetamol prescribing. 38% of all errors were due to 'incorrect frequency' followed by 'unadministrable dosage' (17.6%) and 'incorrect dosage' (14%). Paracetamol, Prednisolone, Methylprednisolone, Ranitidine Morphine, Nystatin and Alfa-Calcidol were the 7 most incorrectly prescribed drugs. There was no significant difference between the performance of the previous and subsequent trainees (p=NS). Conclusions: The majority of errors were made by the SpRs during the weekday daytime however the error rate at night was disproportionately high. The most common error encountered was 'incorrect frequency' followed by 'unadministerable dosage'. Recommendations: Reinforcement of safe prescribing at junior doctors' induction. Structured training of EPR for all junior doctors (renal and non-renal), highlighting common mistakes/prescribing errors. Senior pharmacist briefing on common errors at the end of the grand round. Modification of EPR program to facilitate correct and complete prescribing. Planned re-audit following implementation of these actions.